Formulasi dan Evaluasi Sediaan Topikal Nanogel Mengandung Zinc Oxide Nanopartikel Ekstrak Air Kulit Duku (Lansium domesticum Corr) dan Aktivitas sebagai Antimikroba - Celine Joe; Vera Estefania Kaban; Astriani Natalia Br Ginting (Jurnal Anestesi, 2026)
Skin infections caused by pathogenic microorganisms such as Candida albicans and Staphylococcus aureus remain a significant health problem. The excessive use of conventional antimicrobial agents may lead to microbial resistance, therefore alternative therapies that are safer and more effective are needed. This study aimed to formulate and evaluate a topical nanogel preparation containing zinc oxide (ZnO) nanoparticles and aqueous extract of duku peel (Lansium domesticum Corr.) and to determine its antifungal activity against Candida albicans. The research was conducted using an experimental method which included characterization of simplicia, phytochemical screening, extraction using the infusion method, formulation of nanogel with extract concentrations of 2%, 4%, and 6%, particle size analysis using a Particle Size Analyzer (PSA), and antifungal activity testing using the well diffusion method. The characterization results of the simplicia met the standards of Materia Medika Indonesia, while phytochemical screening indicated the presence of secondary metabolites such as alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. The PSA results showed that the nanogel particle size ranged from 35.85–48.45 nm, indicating that the formulation belongs to the nanoparticle system. The antifungal activity test demonstrated that all nanogel formulations were able to inhibit the growth of Candida albicans, with average inhibition zone diameters of 17.16 mm (2%), 17.22 mm (4%), and 18.84 mm (6%). In conclusion, the nanogel containing ZnO nanoparticles and aqueous extract of duku peel showed good physical characteristics and demonstrated potential antifungal activity, indicating its potential development as a topical preparation for the treatment of fungal skin infections.